Сприйняття Шевченка в малоросійському середовищі ХІХ ст. - Харчук, Р. (Слово і Час, 2020)
У статті здійснено спробу диференційовано розглянути малоросійський дискурс у сприйнятті Шевченкової творчості на матеріалі джерел особистого походження, на прикладі публічної полеміки довкола питання українофільства й української мови включно з донесеннями до ІІІ відділення на цю тему. Визначено такий спектр малоросійського дискурсу в потрактуванні доробку Шевченка: амбівалентне ставлення, спроба поєднати повагу до поета з лояльністю до російського імператора й імперії, гостро негативне і зневажливе намагання відокремити Шевченка від українофільства, української мови й літератури, розуміння Шевченка як предтечі українофільства. Присутність імені поета в донесеннях до ІІІ відділення свідчить, що його ім'я, як і питання української мови, культури чи освіти, російські імперські структури традиційно переносили в площину політичну, остерігаючись розвитку українського сепаратизму. The paper deals with the perception of Shevchenko’s works in the ‘Little Russian’ environment of the 19th century. The interpretations within this social group may be defined as profane because its representatives treated Shevchenko exclusively in the limits of ethnography and as a poet of the common people, while his artistic, national, and political signifi cance was obscured. The author refers to private, public, and secret documents. These are P. Seletskyi’s memoirs; P. Galagan’s journal; the correspondence of K. Kersten with her cousin, member of Cyril and Methodius Brotherhood O. Markovych; M. Rigelman’s polemical paper on Ukrainophilism; T. Florynskyi’s work on Ukrainian language and Ukrainian literary separatism; the notes on the Ukrainophile movement by M. Yuzefovych. The following spectrum of ‘Little Russian’ discourse regarding Shevchenko has been defined: ambivalent attitude (P. Seletskyi); an attempt to combine respect for Shevchenko with loyalty to the Russian emperor and empire (H. Galagan); strictly negative and arrogant attitude (K. Kersten); attempts to separate Shevchenko from Ukrainophilism, Ukrainian language and literature (M. Rigelman and T. Florynskyi), understanding of Shevchenko as a creator of Ukrainophilism (M. Yuzefovych). The presence of the poet’s name in reports to the 3rd Department indicates that apprehending Ukrainian separatism, the Russian imperial structures traditionally treated Shevchenko at the political level, just like issues of the Ukrainian language, culture or education. In the context of prohibitions concerning Ukrainian language and culture, the ‘Little Russian’ discourse of interpreting Shevchenko was inevitably politicized and became identified with the imperial one.